2013
DOI: 10.1111/ene.12261
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of intrathecal immunoglobulin synthesis in epilepsy so far classified cryptogenic

Abstract: Humoral immune activation in the CSF compartment was detected in one-third of patients with epilepsy, besides acute symptomatic seizures particularly frequent in cryptogenic epilepsy--an etiology so far defined as not having a detectable cause. Systematic prospective clinical and experimental trials are required to identify antigenic targets and select appropriate patients for which immunotherapy might offer new causal therapeutic options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
0
11
2
Order By: Relevance
“…Little information is available on chronic epilepsies. An immunoglobulin (Ig) synthesis in the cerebrospinal fluid (CSF) compartment has been investigated in only one larger series of patients with epilepsy . We here reassessed the surprising finding of this study.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Little information is available on chronic epilepsies. An immunoglobulin (Ig) synthesis in the cerebrospinal fluid (CSF) compartment has been investigated in only one larger series of patients with epilepsy . We here reassessed the surprising finding of this study.…”
Section: Introductionmentioning
confidence: 68%
“…A recent study detected intrathecal Ig synthesis surprisingly often in patients with epilepsy in general (34.1%), but most frequently in patients with ‘cryptogenic’ epilepsy (45.2%) . For comparison, OCBs were observed in 0–3.9% of patients in published cohorts of patients without epilepsy or any evident inflammatory central nervous system disease .…”
Section: Discussionmentioning
confidence: 97%
“…Consistent with our findings of 5%, Fauser et al [22] found intrathecal IgG synthesis in 4-8% of their patients not related to seizure etiology (cryptogenic, symptomatic, idiopathic) using immunoblot for OCB detection. In contrast, Kowski et al [23] reported intrathecal Ig synthesis in 34% of their patients using silver staining for OCB detection. One explanation for the discrepant frequency may be the inclusion of acute symptomatic seizures (e.g.…”
Section: Discussionmentioning
confidence: 90%
“…In contrast, Kowski et al . reported intrathecal Ig synthesis in 34% of their patients using silver staining for OCB detection. One explanation for the discrepant frequency may be the inclusion of acute symptomatic seizures (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of occipital nerve blocks has offered a new mode of treatment for migraine variants. Epilepsy treatments have transformed the outlook for patients, but there remains a cohort of patients refractory to oral therapies and in whom surgery offers an alternative [170][171][172][173][174][175][176].…”
mentioning
confidence: 99%